Peran Majelis Duduk Setikar Kampung Dalam Penyelesaian Kekerasan Dalam Rumah Tangga: Analisis Perlindungan Korban Dan Kekuatan Hukum Surat Kesepakatan Di Karang Baru Aceh Tamiang - Mawaddah Mawaddah; Aulil Amri; Nurul Fithria; Badrul Munir (Universitas Islam Negeri Sumatera Utara, 2026)
Domestic violence (DV) is a serious problem that impacts the safety of victims and the social stability of the community. Previous studies on customary institutions in Aceh have mainly highlighted their mediating function and social legitimacy, while critical assessment of the legal force of peace agreements and the actual level of victim protection remains limited. In Karang Baru District, Aceh Tamiang Regency, domestic violence cases are often resolved through customary mechanisms involving the Village Sitting Assembly (MDSK). This study aims to analyze the position and role of MDSK in resolving domestic violence and to critically examine the legal force and problems of the guarantee letters resulting from the deliberations, while assessing the extent to which this mechanism genuinely protects victims rather than merely preserving social harmony. This study uses an empirical juridical research method where applicable legal provisions are linked to the realities that occur in society. The results show that MDSK plays a mediator role by prioritizing a family approach and deliberation. However, the settlements outlined in guarantee letters or peace agreements do not fully satisfy the requirements of a valid agreement, are not equivalent to an authentic deed, and cannot halt criminal proceedings, so that they do not have legally binding legal force and are not accompanied by clear sanctions. As a result, protection for victims of domestic violence is not optimal and there is the potential for recurrence of violence. The novelty of this study lies in integrating a socio-legal analysis of the customary institution's role with a normative assessment of the validity and binding force of the peace agreement, an angle that has received limited attention in prior research. This study contributes to the development of legal pluralism, restorative justice, and victim protection studies, and provides a basis for policy formulation. Therefore, it is necessary to strengthen legal regulations, standards for drafting agreements, and synergy between customary institutions and positive law so that deliberation-based resolutions not only maintain social harmony but also guarantee justice and legal protection for victims.